2010
DOI: 10.1007/s11205-010-9740-2
|View full text |Cite
|
Sign up to set email alerts
|

Relative Standing and Subjective Well-Being in South Africa: The Role of Perceptions, Expectations and Income Mobility

Abstract: Subjective well-being, Relative standing, Perceptions, Expectations, Income mobility, South Africa,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 26 publications
4
57
0
Order By: Relevance
“…On average, male respondents tended to be happier than female. This finding seems to be in line with those of Posel and Casale (2011) and Layard (2011). Blaauw and Pretorius (2013), using the National Income Dynamics Survey dataset in South Africa, also found that females overall had lower levels of well-being relative to males, but surprisingly, the interacting variable between married males and married females indicated that married females were happier than their male counterparts.…”
Section: Differences In Average Happinesssupporting
confidence: 93%
See 2 more Smart Citations
“…On average, male respondents tended to be happier than female. This finding seems to be in line with those of Posel and Casale (2011) and Layard (2011). Blaauw and Pretorius (2013), using the National Income Dynamics Survey dataset in South Africa, also found that females overall had lower levels of well-being relative to males, but surprisingly, the interacting variable between married males and married females indicated that married females were happier than their male counterparts.…”
Section: Differences In Average Happinesssupporting
confidence: 93%
“…Inequalities have negative effects on reported happiness in South Africa and other countries too (Posel & Casale, 2011;Sachs, 2012). Societies with low income inequalities tend to be happier, with high levels of trust (Wilkinson & Pickett, 2010).…”
Section: Income and Happinessmentioning
confidence: 99%
See 1 more Smart Citation
“…The ladder question is one of three alternative ways that have been used in surveys to elicit perceived social rankings. With some variation, the ladder question has been used in surveys carried out in Europe (Riffault, 1991), the Philippines (Mangahas, 1995), Russia (Ravallion and Lokshin, 1999;2002), and South Africa (Posel and Casale, 2011). A second alternative, recently applied in Argentina by Cruces, Pérez-Truglia, and Tetaz (2013), is to pose precise questions about an individual's perception of her place in the income distribution.…”
Section: Perceived Social Rankingmentioning
confidence: 99%
“…Subjective social rankings are important in people's lives: perceived social ranking is associated with subjective well-being, which is significantly stronger than objective measures based on reported income (Posel and Casale, 2011). Efforts to ascend in the perceived social ranking through consumption of some goods may distract individuals from more satisfying activities, and may in the end prove illusory (Frank, 1985).…”
Section: Subjectivementioning
confidence: 99%